Determinan yang Mempengaruhi Pneumonia pada Balita Keluarga Perokok di Wilayah Kerja Puskesmas Meuraxa Kota Banda Aceh - Nur Hikmah; Pasyamei Rembune Kala; Ully Fitria (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2025)
Pneumonia is one of the leading causes of mortality in children under five, especially those living in households with active smokers. This study aims to determine the risk of pneumonia in toddlers from smoking families in the working area of Meuraxa Public Health Center, Banda Aceh City. The research used a case-control design with 33 respondents, consisting of 11 cases (toddlers with pneumonia) and 22 controls (toddlers without pneumonia). Data collection was conducted through a structured questionnaire and analyzed using the chi-square test. The findings revealed that the prevalence of pneumonia among toddlers from smoking households was 33.3%. There were significant associations between pneumonia incidence and several factors, including nutritional status (p = 0.024), immunization status (p = 0.034), exclusive breastfeeding (p = 0.027), parental smoking behavior inside the house (p = 0.009), and household ventilation (p = 0.017). Toddlers who were not exclusively breastfed, had poor nutritional status, incomplete immunization, poor air ventilation, and exposure to cigarette smoke at home were at higher risk of developing pneumonia. This study emphasizes the vital role of the family in creating a healthy, smoke-free home environment that supports children's well-being. Community-based interventions and educational programs are essential to prevent pneumonia and improve the quality of life of children, particularly in urban public health areas like Meuraxa.